Swimming exercise protective effect on waterpipe tobacco smoking-induced impairment of memory and oxidative stress - Alzoubi, Karem H.; Halboup, Abdulsalam M.; Alomari, Mahmoud A.; Khabour, Omar F. (Elsevier, 2019)
Waterpipe tobacco smoking (WP) is associated with a vast range of detrimental health effects, including memory impairment and anti-oxidative scavenging dysfunction. Forced swimming exercise (FSE) is known to improve cognitive function and general wellbeing. In this study, we evaluated the neuroprotective effect of FSE on memory impairment induced by exposure to WP in the rat model. Wistar male rats were divided into four groups: fresh air (control), WP exposure, FSE, and WP/FSE. Animals were exposed to WP for 1 h/day, 5 days/week for 4 weeks. At the same time, animals were forced to swim 1 h/day as 5 min swimming followed by 5 min rest, 5 days/ week for 4 weeks. Spatial learning and memory was assessed using Radial Arm Water Maze (RAWM). Additionally, hippocampal oxidative stress biomarkers including reduced glutathione (GSH), oxidized glutathione (GSSG), GSH/GSSG ratio, glutathione peroxidase (GPx), Catalase, and TBARS were analyzed. Key findings: this study showed that WP exposure impaired both short- and long-term memory (P < 0.05). On the other hand, FSE prevented memory impairment induced by WP exposure (P < 0.05). Moreover, WP exposure reduced activity of catalase, GPx, and GSH/GSSG ratio (P < 0.05) in the hippocampus, which were also normalized by FSE. However, no changes were detected in GSH and TBARS levels in WP exposure and/or FSE groups. In conclusion, WP exposure induced both short- and long- term memory impairments, which was prevented by FSE. This improvement in memory function might be attributed to oxidative stress biomarkers pathways.